Алгоритми відключення трифазних трансформаторів та процеси, що їх супроводжують - Халіков, В.А. (Технічна електродинаміка, 2013)
Розглядаються процеси зміни стану магнітопроводу при відключенні від мережі живлення трифазного трансформатора з чотирипровідною системою під’єднання його первинних обмоток. Показано способи зменшення залишкової намагніченості осердя після знеструмлення трансформатора. Проведено візуальне моделювання процесів засобами програмного пакету MATLAB та запропоновано заходи щодо мінімізації їхньої тривалості. Рассматриваются процессы изменения состояния магнитопровода при отключении от сети трехфазного трансформатора с четырехпроводной системой подключения его первичных обмоток. Показаны способы уменьшения остаточной намагниченности сердечника после обесточивания трансформатора. Проведено визуальное моделирование процессов средствами программного пакета MATLAB и предложены меры по минимизации их продолжительности. The processes of change state of magnetic core when disconnected from the mains three-phase transformer with four-system connecting its primary windings. Ways of reduction of residual magnetization of the core after transformer shutdown are shown. Means of visual simulation shows identity processes recession residual magnetic flux in the single-phase and three-phase transformers. Dependences of the steepness of recession of a magnetic stream after disconnection of the transformer from the size of loading and current of idling of the transformer are given. It is shown that the gap between the neutral conductors on the secondary side of the transformer is an effective tool for the rapid decline of the residual magnetic flux. The nature of this process does not change depending on the load of the three-phase transformer. Visual modeling of transient processes is done with MATLAB and proposes measures to minimize the duration of the processes.